INDUSTRIAL APPROBATION OF COMBINED COUNTERSINK-TAP TOOL - Nurulla M. Vagabov; Ali Z. Kurbanov; Marina A. Magomedovа (Вестник Дагестанского государственного технического университета: Технические науки)
Abstract. Objectives Based on a critical analysis of the results of complex studies, we set out to demonstrate the advantages, as compared with existing technologies, of a developed technology that uses a new cutting scheme with a combined countersink-tap tool. Methods One way to improve the processing capacity, tool life and quality of a cut thread is to reduce the torque and strain hardening of the processed material by employing a new cutting approach to completely eliminate the friction of the lateral sides of the tooth on the surface of the cut thread. It was necessary for this technology to be checked in real production conditions. Results The conducted production tests of a combined countersink-tap tool with the new cutting scheme developed by the inventors have shown that, as a result of a significant reduction in the torque and a decrease in the strain hardening of the processed material, it is possible to increase the cutting speed and increase labour productivity by more than 2 times as compared with the thread cutting processes using taps with staggered teeth, 1.2 times as compared to taps with a corrected structure, and more than 6 times as compared to standard taps. At the same time, the stability of the tool is increased 3-5 times and the number of breakages is also sharply reduced. Conclusion It has been established that the accuracy of the geometric parameters as well as the strength and quality of the thread surface cut by the combined countersink-tap tool with the new cutting scheme in hard-to-work materials is much higher than the same thread parameters obtained by processing with standard and other known taps. The studies also indicated its high reliability, operability and expediency of application for processing the above-mentioned materials. The advantages of the combined tool also include a reduction in thread cutting time as compared to a separate machining of the threaded hole (countersinking with a standard countersink followed by subsequent tapping).